New Clues on the Model of YY Her after two Seasons - Hric, L.; Gális, R.; Dobrotka, A.; Simon, V.; Petrík, K.; Niarchos, P.; Velic, Z.; Gazeas, K.; Smelcer, L.; Hájek, P.; Sobotka, P.; Koss, K.; et al. (2004)
During two observational seasons of international campaign of YY Her we secured photometric data which covered the primary as well as the secondary minima and revealed unexpected outburst activity of this system.
Keywords: Campaign; Photometry; Stars: Individual (YY Her); Stars: Symbiotic